A new cauliflorous species of Psidium (Myrtaceae) from the Atlantic Forest - Tuler, Amélia Carlos; Souza, Marcelo Da Costa; Carrijo, Tatiana Tavares; Peixoto, Ariane Luna (Phytotaxa, 2017)
This paper reports a new species of Psidium found only in the Atlantic Forest of Espírito Santo and Rio de Janeiro, Brazil. Psidium grazielae is related to P. cauliflorum, differing mainly by membranaceous to chartaceous leaves with glandular dots visible on both faces, inconspicuous secondary veins, as well as the absence of trichromes on branches, inflorescences and fruits. We provide the description and illustrations for this new species. The relationship of P. grazielae and P. cauliflorum is discussed, and comments concerning the taxonomy and ecology of the new species are provided.